LncRNA‐MALAT1 Promotes Angiogenesis of Thyroid Cancer by Modulating Tumor‐Associated Macrophage FGF2 Protein Secretion - Huang, Jian‐kang; Ma, Ling; Song, Wen‐hua; Lu, Bang‐yu; Huang, Yu‐bin; Dong, Hui‐ming; Ma, Xiao‐kai; Zhu, Zheng‐zhi; Zhou, Rui (Journal of cellular biochemistry, 2017)
ABSTRACT Tumor‐associated macrophages (TAMs) in the tumor microenvironment have been associated with enhanced tumor progression. In this study, we investigated the role and molecular mechanisms of MALAT1 in TAMs derived from thyroid cancer. The expression of MALAT1 and FGF2 in thyroid cancer tissues and cells were measured by quantitative real‐time PCR and Western blot. TAMs were transfected with indicated constructs. Then the culture medium (CM) from TAMs was harvested for assay. Secreted FGF2 protein levels and TNF‐α, IL‐12, and IL‐10 levels were detected by ELISA. The cell proliferation, migration, and invasion of FTC133 cells were determined with a CCK‐8 assay and a Transwell assay, respectively. In addition, HUVEC vasculature formation was measured by matrigel angiogenesis assay. The higher levels of MALAT‐1 and FGF2 were observed in thyroid cancer tissues and in thyroid cancer cells compared to that in the control. Besides, in the presence of si‐MALAT1, the levels of TNF‐α and IL‐12 were significantly up‐regulated whereas IL‐10 was down‐regulated in the CM from TAMs. Moreover, down‐regulation of MALAT1 in TAMs reduced proliferation, migration, and invasion of FTC133 cells and inhibited angiogenesis. However, overexpression of FGF2 blocked the effects of MALAT1 siRNAs on cell migration, invasion, and angiogenesis. Our results suggest that MALAT1‐mediated FGF2 protein secretion from TAMs inhibits inflammatory cytokines release, promotes proliferation, migration, and invasion of FTC133 cells and induces vasculature formation. J. Cell. Biochem. 118: 4821–4830, 2017. © 2017 Wiley Periodicals, Inc. Our data suggest that MALAT1‐mediated FGF2 protein secretion from TAMs inhibits inflammatory cytokines release, promotes proliferation, migration, and invasion of thyroid cancer cells and induces vasculature formation. Our results demonstrate that these molecules could become new biomarkers and could be used in cancer therapy against the progression of thyroid cancer.